2014
DOI: 10.1051/shsconf/20141201052
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Snorkeling Experience in Pulau Payar Marine Park, Kedah, Malaysia

Abstract: Abstract. Marine Parks in Malaysia receive almost 7.4 million tourists for the past ten years from all over the world. Continuous growth in the number of tourists and mass tourism has resulted in uncontrolled number of tourists, sometimes surpassing the carrying capacity of the site. Due to the lack of control and enforcement, many tour boat operators are bringing snorkelers to small fragile sites at the same timeframe. Such situation has resulted in reduced quality of tourist experience and satisfaction level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…As far as we know, only nine papers have directly explored visitor experience and perspectives. For example, Salim, Mohamed, and Abdullah () investigated the importance of tourists feeding fish while snorkelling in a marine park in Malaysia and found that it was of low importance when compared to the overall snorkelling experience.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As far as we know, only nine papers have directly explored visitor experience and perspectives. For example, Salim, Mohamed, and Abdullah () investigated the importance of tourists feeding fish while snorkelling in a marine park in Malaysia and found that it was of low importance when compared to the overall snorkelling experience.…”
Section: Discussionmentioning
confidence: 99%
“…Visitor satisfaction at fish feeding locations has also been found to be connected with the condition of facilities (Salim et al, ). Lewis and Newsome () reported that visitors were also concerned about the welfare of stingrays and were opposed to the site becoming commercialized, yet they wanted the feeding to continue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations